Caregiving burden in schizophrenia: Is hospital admission effective in reducing it? - Mishra, SK; Pandey, AK; Adhikari, BR; Nepal, S (Journal of Psychiatrists' Association of Nepal, 2018)
Introduction: Caregivers of patients with schizophrenia suffer from significant physical and emotional turmoil. Very less has been done to see if there is some change in their problems once the patient is treated. Material and Method: 36 caregivers of patients with schizophrenia admitted in the psychiatry ward, BPKIHS were enrolled and assessed using BAS at admission and at discharge. Results: The number of caregivers suffering from severe burden had gone down from 17(47.2%) to 1(2.8%) at discharge. There was a significant reduction in the mean scores of all domains of burden. Conclusion: The caregivers suffered from significantly less burden at discharge. However, they need continuous support throughout the treatment period as burden was reduced but not absent. J Psychiatrists’ Association of Nepal Vol .6(1), 2017, p.29-32